METODE BELAJAR MATEMATIKA (VERSI SAYA) - Asmaningtias, Yeni Tri (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2010)
Learning is not had to use reference books, books dictate, and various books that fit with the material. Learning methods can hear, see or daydreaming the subjects. How to learn something like that could be obtained by seeing or hearing other people's experiences. Experiences can be gained from the other person will create excitement for learning mathematics and foster good mental, especially those are known as leaders in mathematics and other scientists. In addition, the study by first identifying the correct way of learning can encourage understanding how to learn mathematics is good, able to understand the scientific definition, characteristics, and description of mathematics. So that people will not be wrong to choose how to learn, able to know the strategies and methods of mathematics will have an impact also on our favorite mathematics.Key word: learning, mathematics